Fabrication of UV-Crosslinked Flexible Solid Polymer Electrolyte with PDMS for Li-Ion Batteries - KAHRAMAN, MEMET VEZİR (MDPI, 2020)
Conventional carbonate-based liquid electrolytes have safety issues related to their high flammability and easy leakage. Therefore, it is essential to develop alternative electrolytes for lithium-ion batteries (LIBs). As a potential candidate, solid-polymer electrolytes (SPEs) offer enhanced safety characteristics, while to be widely applied their performance still has to be improved. Here, we have prepared a series of UV-photocrosslinked flexible SPEs comprising poly(ethylene glycol) diacrylate (PEGDA), trimethylolpropane ethoxylate triacrylate (ETPTA), and lithium bis(trifluoromethane sulfonyl)imide (LiTFSI) salt, with the addition of polydimethylsiloxane with acrylated terminal groups (acryl-PDMS) to diminish the crystallinity of the poly(ethylene glycol) chain. Polysiloxanes have gained interest for the fabrication of SPEs due to their unique features, such as decrement of glass transition temperature (T-g), and the ability to improve flexibility and facilitate lithium-ion transport. Freestanding, transparent SPEs with excellent flexibility and mechanical properties were achieved without any supporting backbone, despite the high content of lithium salt, which was enabled by their networked structure, the presence of polar functional groups, and their amorphous structure. The highest ionic conductivity for the developed cross-linked SPEs was 1.75 x 10(-6) S cm(-1) at room temperature and 1.07 x 10(-4) S cm(-1) at 80 degrees C. The SPEs demonstrated stable Li plating/stripping ability and excellent compatibility toward metallic lithium, and exhibited high electrochemical stability in a wide range of potentials, which enables application in high-voltage lithium-ion batteries.
Keywords: solid polymer electrolyte; polydimethylsiloxane; ion conductivity; lithium-ion battery; flexible battery; POLYSILOXANE; TRANSPORT